Pelatihan Manajemen Sekolah Lansia Matahari Desa Sridadi Kecamatan Sirampog - Pribadi, Prayoga; Setiawan, Ito; Puspasari, Fida Dyah; Majid, Muhamad Nurkholis; Assafi’i, Mochammad Rizqi; Hardian, Sakhrul Rifan (Universitas Pahlawan Tuanku Tambusai, 2025)
One of the flagship programs of Sridadi Village is the senior School. The